Isu-isu penempatan kanak-kanak: Pandangan Pegawai Kebajikan Masyarakat di Kedah - Chan, Cheong Chong; Hillaluddin, Azlin Hilma; Herman, Iran (Universiti Utara Malaysia, 2003)
The purpose of this study is to explore the opinions of Kedah's Pegawai Kebajikan Masyarakat (Social Welfare Officers) regarding three issues concerning placement of children (i.e. adoption and foster care) namely inter-ethnic placement, age consideration and relationship with biological parents. Eleven respondents participated in this study. Data was collected using questionnaire distribution and selective face-to-face or telephone interviews. In general, the responses corresponded with global social work values regarding child welfare. However, the issues of child's best interest and religion were raised when discussing inter-ethnic placement, thus, resulting in disparity in their responses regarding this issue. Majority of the respondents also consented on the difficulty of placing children as they get older. In addition, majority of the respondents agreed that the relationship between adoptive/foster children with their biological parents after placement should be encouraged. However, apprehension about the effects of this relationship to the adoptive/foster family and the child was also highlighted.